2004
DOI: 10.1103/physrevb.69.045324
|View full text |Cite
|
Sign up to set email alerts
|

Generic properties of a quasi-one-dimensional classical Wigner crystal

Abstract: We studied the structural, dynamical properties and melting of a quasi-one-dimensional system of charged particles, interacting through a screened Coulomb potential. The ground state energy was calculated and, depending on the density and the screening length, the system crystallizes in a number of chains. As a function of the density (or the confining potential), the ground state configurations and the structural transitions between them were analyzed both by analytical and Monte Carlo calculations. The syste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
213
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(236 citation statements)
references
References 39 publications
21
213
2
Order By: Relevance
“…Assuming staggering in the x-direction between neighboring rows and inversion symmetry of the y-positions of the rows with respect to the wire axis, the number of minimization parameters is M/2 ((M − 1)/2) for even (odd) number of rows M , and the minimization is straightforward. Within these constraints, the minimization of the energy with respect to the electron configuration reveals 7,8,25 that a one-dimensional crystal is stable for densities ν < 0.78, whereas a zigzag chain forms at intermediate densities 0.78 < ν < 1.71. More rows appear as the density further increases.…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Assuming staggering in the x-direction between neighboring rows and inversion symmetry of the y-positions of the rows with respect to the wire axis, the number of minimization parameters is M/2 ((M − 1)/2) for even (odd) number of rows M , and the minimization is straightforward. Within these constraints, the minimization of the energy with respect to the electron configuration reveals 7,8,25 that a one-dimensional crystal is stable for densities ν < 0.78, whereas a zigzag chain forms at intermediate densities 0.78 < ν < 1.71. More rows appear as the density further increases.…”
Section: Modelmentioning
confidence: 99%
“…Upon increasing density (and, thus, the interaction energy), or weakening the confining potential, the crystal deviates from its strictly one-dimensional structure. It has been shown that at a critical density, a transition to a zigzag crystal takes place 7,11,23,25,26 . Though not for electrons, this zigzag transition has indeed been observed using 24 Mg + ions in a quadrupole storage ring 27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these drawbacks it may be possible to create a one-dimensional Coulomb ring [13] or dusty plasma ring [14] using a two-dimensional (2D) annular potential well. A dusty plasma ring will provide the most direct test of the theory for lattice waves in unbounded Yukawa chains [15], as well as a system with which to explore phenomena such as single-file diffusion [16] and the properties of quasi-one-dimensional systems [17].…”
mentioning
confidence: 99%
“…The long-range Coulomb interaction between electrons becomes relatively important at low electron densities resulting in the formation of a 1D Wigner crystal [2,6,7]. But, the role played by the Coulomb repulsion between electrons is also made greater until it overcomes the confinement potential, as the density is increased, at which point the ground state and one of the excited states are interchanged [8] which may result in hybridization and anticrossing. In Refs.…”
Section: Introductionmentioning
confidence: 99%